AKUNTANSI HIJAU BERBASIS ETIKA BISNIS: IMPLEMENTASI DI RSUA PONOROGO, JAWA TIMUR - Anna Marina; Sentot Imam Wahjono; Gita Desipradani (BALANCE: Economic, Business, Management and Accounting Journal, 2017)
ABSTRACTThis study aimed to test whether business ethics has been owned by an organization to guide the implementation of the Green Accounting and Green Accounting for anything that might be implemented in the hospital. This study used a qualitative approach with phenomenological analysis techniques to process the data collected through in-depth interviews, observation as an outsider, and documentation. Source of data derived from key informants consisted of three people management in the field of procurement or purchase of drugs and medical supplies, 3 directors of hospitals and 10 suppliers. With some guided questions, we examined whether the Business Ethics which has been owned by RSUAP able to serve as the basis for implementing the Green Accounting. This study found evidence that Business Ethics capable and very helpful in implementing the Green Accounting. Accounting field that can be implemented for Green Accounting is the procurement / purchase of medicines and medical supplies as well as cost accounting for waste management. The findings of this research could be used to design other accounting fields that can be implemented in line with the concept of the Green Accounting such as investment and marketing decisions.Keywords : green accounting, Business Ethics, Muhammadiyah hospital.Correspondence to : a_m_rina@yahoo.com, wahjonos@gmail.com, gitadesip@gmail.com